Macroeconomic Dimensions of Public-Private Partnerships - Buffie, Edward (IMF Working Papers; Working Paper ;, 2016)
The voluminous literature comparing public-private partnerships (P3s) and own-investment (OI) by the public sector is dominated by contributions from microeconomic theory. This paper gives macroeconomics a voice in the debate by investigating the repercussions of P3 vs. OI in a dynamic general equilibrium model featuring private capital accumulation and involuntary unemployment with efficiency wages. Typically P3s cost more but produce higher-quality infrastructure and boast a better on-time completion record than OI; consequently, they are comparatively more effective in reducing underinvestment in private capital, underinvestment in infrastructure, unemployment and poverty. The asymmetric impact on macro externalities raises the social return in the P3 2 - 9 percentage points relative to the social return to OI, depending on whether the externalities operate singly or in combination and on whether P3 enjoys an advantage in speed of construction.